IMMUNOLOGY ASPECTS IN TENSION-TYPE HEADACHE CHRONICITY - Susanti, Restu (Biomedical Journal of Indonesia, 2020)
Tension-Type Headache (TTH) headache is a type of primary headache which mostly complained by patients. The pain often ignored due to low mortality rates. Inadequate management makes the pain becoming chronic and causing a high disability rate. Many factors involved in transforming infrequent tension-type headache to chronic tension-type headache. A deeper understanding of the immune system's role in the pathophysiological process and modulation of chronic pain could be a potential target for developing therapies in managing chronic pain.Keywords: chronic tension-type headache, immunology aspect, pathophysiology